Entrepreneurship in Brazil: challenges encountered by French entrepreneurs - Gamiette, Floriane Monica (2020)
This research is focused on the challenges that French entrepreneurs encounter when having a business in Brazil, especially at the opening and while running a business. Brazil has welcomed many French entrepreneurs since the last decade, about 900 subsidiaries are present in Brazil and huge communities of entrepreneurs, such as the French Tech, are performing in the country. Many French entrepreneurs are still interested in going to Brazil to take their chance. That is why, the goal of this research is to provide them with more detailed information from previous entrepreneurs’ experiences, in order for them to better be prepared and diminish the risk of failure. This work is a qualitative study based on qualitative research methodology. Twenty-one semistructured interviews, with open-ended questions, were conducted, which enabled the participant to express its own views and opinions. An increasing number of French entrepreneurs are running a business in Brazil, especially Sao Paulo and Rio where there are various opportunities. That is why this current research is important as its objective is to provide, the coming French entrepreneurs, with better insight and advice to start their journey in Brazil. The objective is to identify the challenges that they might encounter and the things they should be ready for. What has been found is that, indeed, there are numerous challenges to overcome for French entrepreneurs. First, the cultural shock, such as the working relations, then the bureaucracy with the long delays and complex procedures to get important documents or status, the economic instability more than the political one, and the difficulty to find investments from Brazilian investors or the high taxation. However, some good reasons to open a business in Brazil have been mentioned such as the attractiveness of the country, the open-mindedness regarding new business, and last but not least, the quality of life.